Exploring the intersection of utilitarianism and sustainability in business: A conceptual analysis - Artur Yetvart Mumcu (Economics, Management and Sustainability)
Purpose: This research aims to elucidate the benefits commercial entities strive to accrue by implementing sustainability practices, using a conceptual analysis framework to probe into the anticipated benefits underpinning sustainability adoption. Methodology: The study employs a comprehensive literature review to define and establish a framework for utilitarianism and sustainability, focusing on their relationship and implications within the business context. Results: The research findings indicate that sustainability practices can considerably augment the utilitarian objectives of businesses. Energy efficiency initiatives, for instance, can enhance profitability by curtailing energy costs and simultaneously alleviating environmental impacts. Social responsibility endeavours can amplify brand value, solidifying customer loyalty. Elevated employee satisfaction and engagement can foster heightened productivity and competitiveness. Theoretical contribution: This study contributes to the existing body of literature by critically examining the definitions of critical terms and interrogating the ontological validity of the assumed linkage between sustainability initiatives and the anticipated benefits. It also offers a framework illustrating how businesses might integrate the principles of sustainability and utilitarianism, setting a foundation for further exploration of this theme. Practical implications: The research provides valuable insights for businesses seeking to harmonize their activities with environmental, social, and economic impacts in the pursuit of sustainability, while simultaneously aiming to maximize benefits. It underscores the importance of maintaining a delicate equilibrium between sustainability and utilitarianism, as the incorporation of sustainability principles can assist businesses in achieving their profit and benefit creation objectives, thereby fortifying their prospects for enduring success.